Economic and Energy Potential of Sub-Tropical Pine Forest Dry Biomass: A Vital Step in Mitigating Forest Fire Hazards in Indian Western Himalaya - Verma, Amit Kumar; Rawat, Rajneesh; Kaliyathan, Namitha Nhandadiyil; Kumar, Sandeep (Indian Forester, 2024)
Pine forests are among the vegetation types most affected by wildfires, and this is expected to continue as climate change increases the risk of fire. The use of pine needles to produce environmentally friendly products and reduce the risk of forest fires makes ecological, environmental and economic sense. In recent years, there has been a growing interest in finding innovative uses for pine needles. As pine needles are a renewable resource, they offer a sustainable alternative to the traditional materials used in crafting. Their conversion into sustainable products such as paper, mulch, biofuels, etc. not only reduces the accumulation of combustible material in forests but also promotes a circular economy. This approach not only benefits the environment but also provides economic opportunities for local communities living near pine forests. This report explores the dual benefits of using pine needles as a renewable resource. In the field of sustainability, these slender leaves have been transformed into valuable resources, namely bio-briquettes, bio-coal, packaging material, etc. and are also used for the construction of check dams, which are an environmentally friendly alternative to traditional fuels and reduce waste and deforestation. In the field of creativity, artisans use pine needles to create artistic handicrafts and decorative items that give baskets, ornaments, sculptures, etc. a rustic charm. In addition, the beauty and texture of the needles lend themselves to papermaking, creating unique sheets for stationery and artistic purposes. Pine needles are also suitable as an environmentally friendly packaging material due to their durability and fibrousness. The use of pine needles is not only a renewable resource but also offers significant benefits in terms of waste management. The economic viability of this practice is remarkable as it allows local communities to earn an income through the production of pine needles-based products. Additionally, their use in creating environment-friendly products helps reduce the demand for non-biodegradable materials and promotes a greener lifestyle. Furthermore, by removing pine needles from forests, we can successfully limit the accumulation of dry vegetation that might cause forest fires, making it a proactive strategy for managing fire risks and protecting our natural ecosystems.